Cytocompatibility, degradation, mechanical property retention and ion release profiles for phosphate glass fibre reinforced composite rods - Felfel, R.M.; Ahmed, I.; Parsons, A.J.; Palmer, G.; Sottile, V.; Rudd, C.D. (Elsevier, 2013)
Fibre reinforced composites have recently received much attention as potential bone fracture fixation applications. Bioresorbable composites based on poly lactic acid (PLA) and phosphate based glass fibre were investigated according to ion release, degradation, biocompatibility and mechanical retention profiles. The phosphate based glass fibres used in this study had the composition of 40P2O5-24MgO-16CaO-16Na2O-4Fe2O3 in mol% (P40). The degradation and ion release profiles for the composites showed similar trends with the amount of sodium and orthophosphate ions released being greater than the other cations and anions investigated. This was attributed to low Dietzal's field strength for the Na(+) in comparison with Mg(2+) and Ca(2+) and breakdown of longer chain polyphosphates into orthophosphate ions. P40 composites exhibited good biocompatibility to human mesenchymal stem cells (MSCs), which was suggested to be due to the low degradation rate of P40 fibres. After 63 days immersion in PBS at 37 °C, the P40 composite rods lost ~1.1% of mass. The wet flexural, shear and compressive strengths for P40 UD rods were ~70%, ~80% and ~50% of their initial dry values after 3 days of degradation, whereas the flexural modulus, shear and compressive strengths were ~70%, ~80%, and ~65% respectively. Subsequently, the mechanical properties remained stable for the duration of the study at 63 days. The initial decrease in mechanical properties was attributed to a combination of the plasticisation effect of water and degradation of the fibre-matrix interface, with the subsequent linear behaviour being attributed to the chemical durability of P40 fibres. P40 composite rods showed low degradation and ion release rates, good biocompatibility and maintained mechanical properties similar to cortical bone for the duration of the study. Therefore, P40 composite rods have huge potential as resorbable intramedullary nails or rods.